Relativistic scenario for a binary black hole system in blazars. Issue 1 (6th February 2023) - Larios, Bryan; Pérez, Hector; Sacahui, José Rodrigo; Morazán, Bryant; Toralla, Miguel; Ávalos, Jorge
Abstract: Blazars are a type of active galactic nuclei whose jet points toward the observer. Their emission is variable along different time scales and at different wavelengths. Some objects show periodicity in their emission, like the blazar PG 1553+113. In this work, we obtain a periodicity of ∼2.19 years using 12.5 years of data of Fermi‐LAT and then we study a scenario to explain blazar periodicities with timescales of a few years. The scenario is built on a binary supermassive black hole (SMBHs) system where one of the two SMBHs carries a jet. We also assume that one of the two SMBHs has angular momentum and is described by a Kerr metric. We have found estimates for the masses of the sources and the distance separating the two SMBHs.